“Leading Change” - Premi , Harish (Gyan Management Journal, 2020)
This book is written in compelling languageis a ready reckoner for budding managers, students of  business administration and leaders of the organizations to have a thorough understanding of  successful implementation of change in the organizations. The case studies and examples discussed  in each chapter also provide an extra edge to readers as they offer meaningful insights to real life  business problems and their feasible solutions. Key points which are thought-provoking and bring  out the crux of the matter have been separately highlighted to give them prominence.